THE FORMULATION OF CREAM PREPARATIONS BLUSH ON OF ETANOL EXTRACT FROM MIANA PURPLE LEAVES (Coleus scutellarioides L.) AS BLUSHER - Suryanita; Fitrahmia S, Nur; Auliah, Nielma; Bachri, Nurjannah (Journal of Pharmaceutical Science and Herbal Technology, 2024)
Anthocyanin is a chemical compound found in purple miana leaves and plays an important role in providing color. Purple miana leaf extract can be used as a natural coloring in blush on cream preparations. The aim of this research is to determine whether purple miana leaf extract (Coleus scutellarioides L) can be formulated in the form of a blush cream dosage form that is physically and chemically stable. The research method used was experimental research by making blush on preparation formulations with concentrations of 7.5%, 10% and 12.5% ​​and evaluating the preparations using physicochemical, irritation tests and hedonic tests. The research results showed that blush on formulations with concentrations of 7.5%, 10% and 12.5% ​​were physically and chemically stable and in the hedonic/preference test the most preferred formulation was the formulation with a concentration of 12.5%. The conclusion of this research is that the ethanol extract of purple miana leaves (Coleus Scutellarioides L) can be formulated in the form of a blush cream dosage form that is physically and chemically stable.